2015
DOI: 10.1055/s-0035-1563673
|View full text |Cite
|
Sign up to set email alerts
|

Screening and Treatment of Tethered Spinal Cord in Anorectal Malformation Patients

Abstract: Tethered cord occurs in 9% of the ARM patients. Neonatal spinal ultrasonography has a sensitivity and specificity of 80 and 89%, respectively. Not in all patients an MRI was performed, but the vast majority remained clinically asymptomatic concerning TSC. Ultrasound screening seems an effective screening method, however, when ultrasonography is negative and the patient becomes symptomatic later in life, an MRI should be performed to exclude TSC. In our series, only 1 of 110 ARM patients had symptomatic tethere… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2016
2016
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(3 citation statements)
references
References 20 publications
0
3
0
Order By: Relevance
“…The association between ARM and SD has been widely documented in the literature [2,5,10]. The high variability over the years in the reported incidence and in the surgical approach to this spinal anomaly is mainly due to the evolution of the diagnostic and therapeutic techniques.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The association between ARM and SD has been widely documented in the literature [2,5,10]. The high variability over the years in the reported incidence and in the surgical approach to this spinal anomaly is mainly due to the evolution of the diagnostic and therapeutic techniques.…”
Section: Discussionmentioning
confidence: 99%
“…Patients with anorectal malformations (ARM) often present with associated anomalies of the spectrum of the VACTERL association, which includes spinal and/or vertebral defects (V), anorectal malformations (A), congenital cardiac anomalies (C), esophageal atresia/tracheoesophageal fistula (TE), renal and urinary abnormalities (R), and limb lesions (L) [1]. In particular, spinal dysraphism (SD) has been reported in up to 46% of the patients with ARMs [2,3]. Therefore, neonates with ARM are screened at birth for the possible association with the above anomalies, and a spinal ultrasound (US) is performed in the neonatal period to detect spinal anomalies, confirmed or not by magnetic resonance imaging (MRI).…”
Section: Introductionmentioning
confidence: 99%
“…In the Rohrschneider et al study, spinal disorder findings diagnosed in ultrasonography of 30 babies with a mean age of 5.5 months were consistent with MRI findings; in all cases of abnormalities, the diagnoses were the same ( 11 ) Also, in Sattar’s study, the use of prenatal ultrasonography in diagnosis of spina bifida led to favorable results in post-natal follow-up by MRI, so that in all eight infants under study, ultrasonography had diagnosed prenatal spina bifida ( 12 ). In the latest studies in 2015, the Hondel et al study showed that ultrasonography had a sensitivity of 80% and specificity of 89% in diagnosing tethered cord ( 13 ). One of the other items not mentioned in other studies, which has been examined for the first time in this study, is the relationship between spinal cord abnormalities findings in patients with neurogenic bladder on MRI with ultrasonography.…”
Section: Discussionmentioning
confidence: 99%